A Catholic, a Patriot, a Good Modernist: Manuel de Falla and the Francoist Musical Press. (1st June 2013) - Moreda-Rodríguez, Eva
Abstract : On 14 November 1946, the composer Manuel de Falla died in Alta Gracia, in the Argentinean province of Córdoba. He had last seen his Spanish homeland in September 1939, only five months after the end of the Spanish Civil War. Ever since his departure, music critics and journalists back in Spain had been engaging in a strategy which aimed to present Falla as sympathetic to the Francoist cause and — most importantly — as an incarnation of those values which the regime considered the very core of national identity. It is the aim of this article to analyse this strategy, which was not only a reflection of the ways in which Francoism shaped Spanishness, but also a continuation of conceptions of national identity which predate Franco. The treatment of Falla across a range of periodical publications (from the music criticism sections of newspapers to specialized music periodicals), from his departure to Argentina in September 1939 to his funeral in Cadiz on 9 January 1947, will be analysed, focusing on three main themes which made it possible for the Francoist press to appropriate the composer: the mysticism allegedly inherent to Falla's work and persona; the Castilianism latent in his El Retablo de Maese Pedro ; and the ways in which Falla's music could incarnate a truly Spanish and 'acceptable' modernism, valid as a model for Spanish young composers. El 14 de noviembre de 1946, el compositor Manuel de Falla murió en Alta Gracia, en la provincia argentina de Córdoba. Había vivido fuera de España desde septiembre de 1939, solo cinco meses después de terminar la Guerra Civil. Desde su marcha, los críticos musicales y periodistas españoles habían tratado de presentar a Falla como un defensor de la causa franquista y, especialmente, como la encarnación de los valores que el régimen consideraba centrales en la identidad nacional española. El objetivo de este artículo es analizar esta estrategia, que no era solamente un reflejo de la forma en la que el Franquismo con- cebía la Hispanidad, sino también una continuación de conceptos de identidad nacional que preceden al Franquismo. Se analizará el tratamiento de Falla en una variedad de publicaciones periódicas (desde las secciones de crítica musical de periódicos hasta publicaciones periódicas especializadas en música), desde su marcha a Argentina en 1939 hasta su funeral en Cádiz el 9 de enero de 1947, centrándose en tres temas principales que fueron los que permitieron a la prensa franquista apropiarse del compositor: el misticismo supuestamente intrínseco en la obra y personalidad de Falla; el castellanismo latente en El Retablo de Maese Pedro ; y la forma en que Falla podía encarnar un modernismo auténticamente español y aceptable que sirviese de modelo para los jóvenes compositores españoles.